COMPANY STRATEGY IN DEVELOPING HUMAN RESOURCE MANAGEMENT AND WORK MOTIVATION AS AN EFFORT TO IMPROVE AN EMPLOYEE PERFORMANCE (CASE STUDY OF TRAINING MANAGEMENT AT PT. SMF, WEST JAKARTA BRANCH) - Nuraini, Siti; Kasmir, Kasmir (Dinasti International Journal of Management Science, 2020)
Those company's strategy in developing human resource management and work motivation as an effort to improve employee performance is absolutely needed at PT. SMF because as one of a company which engaged in financial . Its urges to have an employees who are competent on their fields so it would be able to improve those results which have been targeted and accordance to company's vision and mission. This research has purpose to explored the stages of human resource development strategies and work motivation for employees in delivered good performance results. This because most employees are working directly to the field and face to face with market conditions. Those analysis result shows that those strategy has been applied and implemented but still lowest in terms of work motivation because some employees who does not attend those training management their career paths are still not widely open so motivation still relying on bonuses with same value for each division.